Effect of Crud Colicin Extracted From Escherichia coli on Phagocytosis in Uitro - AI Mohymen, N. A; Hussain, H; essa, R (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The effect of crude colicin extracted from E. coli isolated from urinary tract infection patients on phagocytosis in vitro was studied . Results showed that the effect of crude colicin on phagocytic cells and their activities were concentration dependent. Low concentration (50 Mg/ml) have no significant effect (p>O.OS) on shape, size, migration and engulfment activity of phagocytic cells, while (50, 100 Mg/ml) enhanced killing activity and increase superoxide ( 02 ) production as indicated by (NBT) test. But high concentration (500 mg/ml) of crude colicin caused inhibition of phagocytic cells activities, that leads to inhibition in non-spesfic immunity.